Bahasa Inggris - Firda Ruhul Aflah; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to examine the effectiveness of the PAREPIA teaching aid in enhancing fifth-grade students' conceptual understanding of the human respiratory system. A quantitative approach employing a quasi-experimental nonequivalent control group design was conducted with 64 fifth-grade students, comprising 32 students in the experimental class and 32 students in the control class. Data were collected using a 25-item multiple-choice test administered as a pretest and posttest. The data were analyzed using the Rasch Model with stacking analysis through Winsteps 4.8.2 to evaluate changes in students' conceptual understanding. The results showed that the experimental class achieved greater conceptual gains than the control class. The mean measure increased from 0.28 to 1.70 logits (+1.42 logits) in the experimental class, whereas the control class increased from 0.24 to 1.19 logits (+0.95 logits). These findings indicate that the PAREPIA teaching aid effectively facilitates students' conceptual understanding by providing interactive, hands-on learning experiences that help transform abstract concepts into concrete understanding. Therefore, the PAREPIA teaching aid is effective in improving fifth-grade students' conceptual understanding of the human respiratory system and contributes to enhancing the quality of elementary science education.